TEACHERS’ PEDAGOGICAL COMPETENCE IN IMPLEMENTING ACTIVE AND ENJOYABLE LEARNING IN ISLAMIC JURISPRUDENCE EDUCATION - Novi Asmaul Khasanah; Arditya Prayogi; Riki Nasrullah (CV. Mitkom Indotama, 2026)
The quality of Islamic jurisprudence (fiqh) learning in Islamic Junior High Schools (Madrasah Tsanawiyah), particularly at MTs Al-Utsmani Kajen, Pekalongan, faces challenges due to low student interest, who consider fiqh to be repetitive material, and limited infrastructure. This article aims to analyze the pedagogical competence of fiqh teachers in creating active, innovative, creative, effective, and enjoyable learning (PAIKEM). This article uses a descriptive qualitative approach, data were collected through interviews, observations, and documentation, involving the principal, Islamic religious education teachers, and students as informants. The results show that fiqh teachers have good pedagogical competence in understanding student characteristics, applying learning theories, developing curricula, and using engaging teaching strategies, such as digital media, to increase student participation. However, limited facilities and low student active involvement hinder the full implementation of PAIKEM. Internal factors, such as teacher motivation and educational background, as well as external factors, including principal support and professional development, significantly influence teaching effectiveness. Strengthening these factors through the integration of technology, contextual strategies, and systemic support is necessary to create meaningful, inspiring Islamic jurisprudence (fiqh) learning that is able to shape students' Islamic character in accordance with current demands.